Endoscopic decompression of middle nerve in patients with carpal tunnel syndrome - Tsymbaliuk, Vitaliy; Chyrka, Iurii (Ukrainian Neurosurgical Journal, 2015)
Purpose. Results of endoscopic surgical treatment evaluation in patients with carpal tunnel syndrome. Materials and methods. For median nerve decompression in the carpal tunnel endoscopic technique and K.G. Krishnan tools were selected. The detailed technique of endoscopic intervention using carpal approach is described. The results of 34 patient’s treatment with carpal tunnel syndrome (CTS) were analyzed. Results. Patients’ state was evaluated before surgery, on the 7 and 30 days after surgery. Regression of neuropathic pain, according to the questionnaire BCTQ, was observed in all operated patients. Functional outcome worsened on the 7day after surgery, but in a month later patients reported significant improvement in hand function that corresponds to changes in control electroneuromyography and ultrasound scanning of the middle nerve. In one case after surgery hypoesthesia regression was not achieved. Conclusions. Endoscopic technique is a method of choice in patients with CTS. Due to miniinvasive approach and sufficient carpal tunnel visualization, it can be successfully used in routine neurosurgical practice. Treatment results indicate efficacy of endoscopic method and fast rehabilitation of the patients.